منهج السنة النبوية في الوقاية من الانحرافات الجنسية : دراسة تحليلية تطبيقية - Roshayati Rasdi (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
Progress and globalization have resulted in rampant social problems such as sexual deviations which occur all over the world, including Muslim countries. This situation has deepened until it becomes a familiar phenomenon of people imitating the West. The lesbians, gays, bisexuals, and transgenders, for example, have made recent demands on government and society for their rights in public, under the name of LGBT. This research therefore, aims to emphasize implementable methods of prevention from sexual deviations from the Hadith of Nabawiyyah as well as the opinions of scholars as the Sunnah provides guidance and direction to resolve these issues. The researcher uses inductive, descriptive, and analytical approaches to examine youths and their status, and their relation to sexual deviations, as well as to explain types of sexual deviations and their factors that lead to them. We can be guided regarding the problem on sexual deviations and its prevention through the methodology of the Sunnah which includes proper and sound home education, selfimmunization, religious guidance and counseling, and the role played by the state.